1989
DOI: 10.1128/iai.57.3.845-849.1989
|View full text |Cite
|
Sign up to set email alerts
|

Role of tryptophan degradation in respiratory burst-independent antimicrobial activity of gamma interferon-stimulated human macrophages

Abstract: To determine whether extracellular tryptophan degradation represents an oxygen-independent antimicrobial mechanism, we examined the effect of exogenous tryptophan on the intracellular antimicrobial activity of gamma interferon (IFN-y)-stimulated human macrophages. IFN-y readily induced normal monocyte-derived macrophages (MDM) to express indoleamine 2,3-dioxygenase (IDO) activity and stimulated MDM, alveolar macrophages, and oxidatively deficient chronic granulomatous disease MDM to degrade tryptophan. All IFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
3

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(89 citation statements)
references
References 29 publications
2
81
3
Order By: Relevance
“…In addition, our data provide a further example of the differences existing between brain microglia and macrophages of peripheral origin in their specific functions in response to immune stimuli. In contrast to other reports (Murray et al, 1989), which failed to detect any IDO activity in murine macrophages on stimulation with IFN-y, we report here that IDO is induced by this cytokine in murine macrophages and microglial cells. Although variations may exist among the cell lines studied, a recent report has shown that peritoneal macrophages from the mouse are able to catabolize L-tryptophan to L-kynurenine on IFN-y treatment, an effect that was particularly evident in the presence of NO synthase inhibitors (Thomas et al, 1994;see below).…”
Section: Alberati-giani Et Alcontrasting
confidence: 99%
“…In addition, our data provide a further example of the differences existing between brain microglia and macrophages of peripheral origin in their specific functions in response to immune stimuli. In contrast to other reports (Murray et al, 1989), which failed to detect any IDO activity in murine macrophages on stimulation with IFN-y, we report here that IDO is induced by this cytokine in murine macrophages and microglial cells. Although variations may exist among the cell lines studied, a recent report has shown that peritoneal macrophages from the mouse are able to catabolize L-tryptophan to L-kynurenine on IFN-y treatment, an effect that was particularly evident in the presence of NO synthase inhibitors (Thomas et al, 1994;see below).…”
Section: Alberati-giani Et Alcontrasting
confidence: 99%
“…In addition, we found that human monocytes did not release NO2^ after infection with T. gondii (data not shown). Tryptophan degradation contributes to the antimicrobial activity of IFN-7-activated human MDM toward T. gondii, but this is not the case for human monocytes [20].…”
Section: Discussionmentioning
confidence: 97%
“…In addition to general amino acid depletion, host cells can also specifically deplete intracellular tryptophan during pathogen invasion (Hayashi et al, 2001;Silva et al, 2002). Tryptophan depletion as an anti-bacterial mechanism was first described in Chlamydia-infected cells (Byrne et al, 1986;Murray et al, 1989;Beatty et al, 1994). The addition of interferon-gamma (IFN-g) to infected cells almost completely abolishes intracellular chlamydial growth.…”
Section: The Mechanismsmentioning
confidence: 99%
“…Early investigations on the role of tryptophan and IDO in driving aberrant form differentiation yielded mixed results. While some groups found tryptophan supplementation alone could reverse the effects of IFN-g, others found no effect (Murray et al, 1989). When the C. trachomatis genome was sequenced -and especially when multiple clinical strains were sequenced -a major clue emerged.…”
Section: Pathogen Responses To Host Aa Starvationmentioning
confidence: 99%